Elevated triglyceride-glucose (TyG) index predicts impaired islet β-cell function: A hospital-based cross-sectional study - Chen, Zi; Wen, Jie (Frontiers in Endocrinology, 2022)
Objective: To explore the relationship between the TyG index and the insulin secretion function of pancreatic β-cells, and to determine the possibility of the TyG index in predicting β-cell dysfunction and the development of diabetes. Methods: A cross-sectional study was performed among 914 participants who took their annual health checkups at the Third Xiangya Hospital. The early- and late-phase pancreatic β-cell secretion was assessed based on the results of the oral glucose tolerance test (OGTT). In addition to anthropometric parameters and laboratory parameters, information about health-related habits and disease histories was obtained from the National Physical Examination Questionnaire. Pearson correlation analysis was used to study the relationship between the TyG index and pancreatic β-cell function. The receiver operating characteristic (ROC) curve was used to calculate the cut-off points of the TyG index in predicting β-cell dysfunction. According to the OGTT results and medical history， the participants were categorized into three groups: the normal glucose tolerance group (NGT, n=276), the impaired glucose regulation group (IGT, n=323), and the diabetes group (DM, n=315). The correlation between the TyG index and β-cell function among the three groups and the association between the TyG index and glucose metabolic conditions were further explored. Results: The TyG index was negatively correlated with the indexes that reflect the early and late secretory function of β-cells, not only in the NGT group but also in the IGT and DM group. The minimum cut-off values for the TyG index to identify the risk of early- and late-phase β-cell dysfunction are 9.08 and 9.2 respectively. The TyG indexes of the IGT and DM group were higher than that of the NGT group, and with the growth of the TyG index, the risk of prediabetes and diabetes was increased significantly. Conclusion: Increased TyG index is associated with impaired β-cell function regardless of the glucose metabolic conditions. The TyG index is an alternative indicator for predicting β-cell dysfunction.